2013
DOI: 10.1155/2013/230176
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Human Hydatid Cyst Fluid in a Murine Model of Colon Cancer

Abstract: This study evaluates the antitumor immune response induced by human hydatic cyst fluid (HCF) in an animal model of colon carcinoma. We found that anti-HCF antibodies were able to identify cell surface and intracellular antigens in CT26 colon cancer cells. In prophylactic tumor challenge experiments, HCF vaccination was found to be protective against tumor formation for 40% of the mice (P = 0.01). In the therapeutic setting, HCF vaccination induced tumor regression in 40% of vaccinated mice (P = 0.05). This vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 36 publications
(35 reference statements)
4
43
0
6
Order By: Relevance
“…We have recently found that immunization with mucin peptides derived from the helminth parasite Echinococcus granulosus can potently induce antitumor activity by increasing the frequency of activated NK cells and endowing splenocytes with the capacity to mediate killing of tumor cells . In addition, we observed that vaccination with E. granulosus antigens (human hydatic cyst fluid) significantly inhibits colon cancer growth (both in prophylatictic and therapeutic settings) via induction of antitumor immunity . Interestingly, mice immunized with hydatic cyst fluid developed specific antibodies capable of recognizing tumor cells, consistent with previous reports indicating that parasites and cancer cells share common antigens …”
supporting
confidence: 90%
See 1 more Smart Citation
“…We have recently found that immunization with mucin peptides derived from the helminth parasite Echinococcus granulosus can potently induce antitumor activity by increasing the frequency of activated NK cells and endowing splenocytes with the capacity to mediate killing of tumor cells . In addition, we observed that vaccination with E. granulosus antigens (human hydatic cyst fluid) significantly inhibits colon cancer growth (both in prophylatictic and therapeutic settings) via induction of antitumor immunity . Interestingly, mice immunized with hydatic cyst fluid developed specific antibodies capable of recognizing tumor cells, consistent with previous reports indicating that parasites and cancer cells share common antigens …”
supporting
confidence: 90%
“…In addition, we observed that vaccination with E. granulosus antigens (human hydatic cyst fluid) significantly inhibits colon cancer growth (both in prophylatictic and therapeutic settings) via induction of antitumor immunity . Interestingly, mice immunized with hydatic cyst fluid developed specific antibodies capable of recognizing tumor cells, consistent with previous reports indicating that parasites and cancer cells share common antigens …”
supporting
confidence: 89%
“…Also it can partially reduce the pathogenesis of the infection and improve the patient's condition in cryptosporidiosis (Riggs et al 1994), schistosomiasis (Wynn et al 1995), malaria (Schofield et al 1993) and American trypanosomiasis (Kumar and Tarleton 2001). In severe cases of the malaria (Schofield et al 1993) and leishmaniasis (Convit et al 1987(Convit et al , 1989, immunotherapy alone or beside chemotherapy, would be a best strategy to reduce the pathophysiology (Berriel et al 2013) 2 Toxocara canis (Darani et al 2009) 3 Acantamoeba castellani (Pidherney et al 1993) 4 Plasmodium yoelli 5 Trypanosoma cruzi (Kallinikova et al 2006;Mel'nikov et al 2004) 6 Toxoplasma gondii (Darani et al 2009;Kim et al 2007;Miyahara et al 1992) of the infection. Another aspect which made immunotherapy as a remarkable method of treatment is drug resistance, which is increasing in parasitic infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, it has been shown that in patients with hydatid cyst, incidence of different cancers was much lower than what exist in normal population [2]. Also the effect of different hydatid cyst antigens on inhi-H bition of the melanoma cancer growth has been reported in animal model [3][4][5] and in cell culture medium [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it has been reported that in experimental animals, hydatid cyst fluid induces antitumor activity against colon cancer [3] and immunization of mice with live protoscolices resulted in significant reduction of melanoma cancer growth in C57/black mice [4]. Also in different investigations, the existence of common antigens such as the Tn antigen, TK antigen and Sial Tn antigen, has been shown between cancer and hydatid cyst [9].…”
Section: Introductionmentioning
confidence: 99%